How Does It Feel to Be a Pathologist in Turkey? Results of a Survey on Job Satisfaction and Perception of Pathology - Burcin PEHLIVANOGLU; Hur HASSOY; Gulen GUL; Umut AYKUTLU; Basak DOGANAVSARGIL (Federation of Turkish Pathology Societies, 2021)
Objective: Job satisfaction affects productivity and professional performance in many aspects; however, there is limited data regarding pathologists' job satisfaction. Hence, in this study, we aimed to evaluate surgical pathologists' job satisfaction in Turkey. Materials and Methods: We conducted a 59-item web-based survey questioning respondents' institutional background, history of training, continuing education status/research activities, physical conditions, professional well-being, and job satisfaction level. Likert-type and open/ close ended questions were asked and scored. The participants were also asked to complete the Minnesota Satisfaction Questionnaire-Short Form. Results: Of the 321 respondents, 75% were female, the median age was 41 years (range 28-71 years), experience as a pathologist ranged between 0.12 and 44 years (mean 11.4±9.16 years). Academic pathologists, senior pathologists with ≥20 years of experience, and pathologists working at large institutions and living in developed cities expressed better physical conditions, higher satisfaction with working conditions and, therefore, higher overall job satisfaction (p<0.05). 98% agreed that pathologists have a critical impact on patient management; however, the majority (>80%) thought that patients barely know what pathologists do and other physicians rarely understand the difficulty and limitations in pathology practice. 82% were happy to have chosen pathology but 45% reported to experience the feeling of being "burnt out". Conclusions: Our findings suggest that younger pathologists are less satisfied with their jobs and a surgical pathologist's job satisfaction increases with the physical and technical quality of the pathology laboratory/institution, and years of experience. Pathologists seem to be aware of their important role in patient management although they think that pathology remains "invisible" to many physicians and patients.